KASABACH-MERRIT syndrome triggered by vaccination - Batali, S.; Aguenaou, H.; Barkat, A. (International Journal of Scientific Research and Management (IJSRM), 2020)
Kasabach-Merritt syndrome is a rare disorder of the newborn or very young child which combines a rapidly expanding red-purple vascular tumor and a hematological syndrome dominated by major thrombocytopenia and more moderate consumption of fibrinogen and coagulation. This syndrome is always considered serious due to hemorrhages related to coagulopathy. Imaging confirms the diagnosis and searches for deep locations. Therapeutic management must be early, multidisciplinary, adapting the benefits to therapeutic risks in order to improve the prognosis. We report the case of a KASABACH-MERRITT Syndrome on a preexisting thigh angioma triggered by vaccination in a female infant treated with angiogenesis SIROLIMUS, to focus on the cause and effect relationship between vaccination and SKM in the light of literature.